Decadent subjects : the idea of decadence in art, literature, philosophy, and culture of the fin de siècle in Europe - Bernheimer, Charles, 1942- (Parallax (Baltimore, Md.), 2002)
Annotation Charles Bernheimer described decadence as a "stimulant that bends thought out of shape, deforming traditional conceptual molds." In this posthumously published work, Bernheimer succeeds in making a critical concept out of this perennially fashionable, rarely understood term. Decadent Subjects is a coherent and moving picture of fin de sïcle decadence. Mature, ironic, iconoclastic, and thoughtful, this remarkable collection of essays shows the contradictions of the phenomenon, which is both a condition and a state of mind. In seeking to show why people have failed to give a satisfactory account of the term decadence, Bernheimer argues that we often mistakenly take decadence to represent something concrete, that we see as some sort of agent. His salutary response is to return to those authors and artists whose work constitutes the topos of decadence, rereading key late nineteenth-century authors such as Nietzsche, Zola, Hardy, Wilde, Moreau, and Freud to rediscover the very dynamics of the decadent. Through careful analysis of the literature, art, and music of the fin de sïcle including a riveting discussion of the many faces of Salome, Bernheimer leaves us with a fascinating and multidimensional look at decadence, all the more important as we emerge from our own fin de sïcle.